Optimal Binding of Acetylene to a Nitro-Decorated Metal–Organic Framework - Duong, Thien D. (J Am Chem Soc, 2018)
[Image: see text] We report the first example of crystallographic observation of acetylene binding to −NO(2) groups in a metal–organic framework (MOF). Functionalization of MFM-102 with −NO(2) groups on phenyl groups leads to a 15% reduction in BET surface area in MFM-102-NO(2). However, this is coupled to a 28% increase in acetylene adsorption to 192 cm(3) g(–1) at 298 K and 1 bar, comparable to other leading porous materials. Neutron diffraction and inelastic scattering experiments reveal the role of −NO(2) groups, in cooperation with open metal sites, in the binding of acetylene in MFM-102-NO(2).